The Dobroe 9 site: a stratified Early Neolithic complex in the upper Don River - Yurkina, Elizaveta; Smol’yaninov, Roman; Kulichkov, Alexey; Kul’kova, Marianna; Zheludkov, Andrey; Yanish, Yevheniia; Shatrovaya, Diana (Acta Geographica Lodziensia, 2020)
The Middle Don Culture, distributed within the Middle and Upper Don River area, is thought to be one of the earliest Eastern European Neolithic cultures, and is dated to the 6th–5th millennium BC. A group of Neolithic sites was found on the right shore of the Voronezh River, and has been named the “Dobroe sites”. The Dobroe 9 settlement is one of few sites in this region at which an assemblage of Middle Don Culture has been recorded in a clear stratigraphic position. The numerous faunal remains, ceramic complex and stone inventory found at this site allows for a reconstruction of the earliest stages of the Neolithic. The elaborated ceramic typology suggests a gradual transformation of the local culture. The particularity of sedimentation process and deposition of artefacts allowed a precise correlation of stone inventory types with early-Neolithic ceramic types. Preliminary reconstructions of palaeoclimate and episodes of human activity for this time period were implemented based on geochemical methods